ANALISIS DAMPAK PERTAMBANGAN NIKEL PT X DI PULAU GAG : Resiko Lingkungan dan Peluang Ekonomi - Nur Salmaida Sangadji; Albert Gamot Malau (Halu Oleo University, 2025)
This study aims to analyse the environmental and economic impacts of nickel mining activities by PT X on Gag Island, Raja Ampat. The research employs a descriptive qualitative approach, with data collected through literature studies from scientific journals, reports by environmental organisations, relevant legal documents, and credible online news articles related to the mining industry and ecological issues. The findings indicate that mining activities have caused significant ecological damage, including coral reef degradation, marine pollution, deforestation, and disruption of ecosystem balance. On the other hand, the presence of the mining company has contributed economically through increased community income, job creation, and the implementation of corporate social responsibility (CSR) programs. Nevertheless, the adverse impacts experienced directly by local communities, especially Indigenous peoples, have triggered strong resistance against the sustainability of mining operations in the region. This condition underscores the importance of a comprehensive evaluation of mining policies in ecologically sensitive areas, taking into account marine ecosystem protection, forest sustainability, and the rights of affected Indigenous communities.